Cell-penetrating peptide sequence and modification dependent uptake and subcellular distribution of green florescent protein in different cell lines - Patel, Sanjay G.; Sayers, Edward J.; He, Lin; Narayan, Rohan; Williams, Thomas L.; Mills, Emily M.; Allemann, Rudolf K.; Luk, Louis Y. P.; Jones, Arwyn T.; Tsai, Yu-Hsuan (Scientific reports, 2019)
Protein therapy holds great promise for treating a variety of diseases. To act on intracellular targets, therapeutic proteins must cross the plasma membrane. This has previously been achieved by covalent attachment to a variety of cell-penetrating peptides (CPPs). However, there is limited information on the relative performance of CPPs in delivering proteins to cells, specifically the cytosol and other intracellular locations. Here we use green fluorescent protein (GFP) as a model cargo to compare delivery capacity of five CPP sequences (Penetratin, R8, TAT, Transportan, Xentry) and cyclic derivatives in different human cell lines (HeLa, HEK, 10T1/2, HepG2) representing different tissues. Confocal microscopy analysis indicates that most fusion proteins when incubated with cells at 10 µM localise to endosomes. Quantification of cellular uptake by flow cytometry reveals that uptake depends on both cell type (10T1/2 > HepG2 > HeLa > HEK), and CPP sequence (Transportan > R8 > Penetratin≈TAT > Xentry). CPP sequence cyclisation or addition of a HA-sequence increased cellular uptake, but fluorescence was still contained in vesicles with no evidence of endosomal escape. Our results provide a guide to select CPP for endosomal/lysosomal delivery and a basis for developing more efficient CPPs in the future.